Map of The Velocity and Direction of Ocean Currents During The East and West Monsoons of Manakarra Beach Mamuju - Rosalina, Dwi; Rombe, Katarina Hesty; Sabilah, Anisa Aulia; Anisya, Ainun (Rekayasa, 2024)
Current characteristics, including the type of dominant current, velocity, and direction, as well as the movement of ocean currents, cause the condition of a body of water to be dynamic. The aim of the study was to calculate the current direction and determine the direction of the west and east monsoon currents at Manakarra Beach in Mamuju. This study used the ARC GIS, Aviso, and MS Excel applications to utilize secondary data. The raw data were downloaded on Aviso to obtain the u and v vectors. The data obtained from Aviso was then processed into the MS Excel application to obtain the direction and velocity of the current. After gaining the current direction and velocity, the data were then visualized in the form of direction and velocity using interpolation analysis in ARC GIS. The results of the study were in the form of current velocities in Manakarra waters in 2022 in the west monsoon (reaching the highest number of 0.876561 m/s and the lowest number of 0.06885 m/s), and in the east monsoon the current velocity reached the highest number of 0.53816 m/s and the lowest number of 0.07355 m/s. In addition, the current direction in Manakarra waters in 2022 in the west monsoon had three directions, namely from the northwest, west, southwest, and ends in the northeast. In the east monsoon, there were three current directions in Manakarra waters, namely from the east, northeast, southeast, and partly from the northwest.